FORMULATION AND EVALUATION OF ORODISPERSIBLE TABLETS OF GRANISETRON HYDROCHLORIDE USING PLANTAGO OVATE AS NATURAL SUPERDISINTEGRANTS - Sahoo, Chinmaya Keshari; Sahoo, Nalini Kanta; Sahu, Madushima; ., V.Alagarsamy; Moharana, Alok Kumar; Sarangi, Deepak Kumar; Satyanarayana, Kokkula (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2016)
The main objective of the study was to develop orodispersible tablets of Granisetron hydrochloride, a selective 5-HT3 receptor antagonist (an antivomiting agent) for improving patient compliance, especially those of paediatric & geriatric categories with difficulties in swallowing. In the wet granulation method orodispersible (ORD) tablets were prepared using natural super disintegrants plantago ovate.The prepared batches of tablets were evaluated for weight variation, hardness, friability, wetting time, in vitro dispersion time, drug content and in vitro dissolution studies. The tablet formulation batch F4 was considered as the overall best formulation (with an in vitro drug release study of 99.11%).Short term stability studies (at 40±2ºC/75±5% RH) on the best formulation indicated that there no significant changes in drug content. From the Fourier Transform Infrared (FTIR) spectroscopy study indicated that there are no drug excipient interactions. Key words: Granisetron hydrochloride, Orodispersible tablets, FTIR spectroscopy, in vitro drug release study.